2019
DOI: 10.1038/s41593-018-0313-z
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated protocadherin-pathway activity as an intrinsic defect in induced pluripotent stem cell–derived cortical interneurons from subjects with schizophrenia

Abstract: We generated cortical interneurons (cINs) from iPSCs derived from14 healthy controls (HC cINs) and 14 patients with schizophrenia (SCZ cINs). Both HC cINs and SCZ cINs were authentic, fired spontaneously, received functional excitatory inputs from host neurons, and induced GABA-mediated inhibition in host neurons in vivo . However, SCZ cINs had dysregulated expression of protocadherin genes, which lie within documented SCZ loci. Mice lacking protocadherin α showed defective arborization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 61 publications
(80 reference statements)
5
91
0
Order By: Relevance
“…We propose a model in which the extent of PCD among cINs is determined by pro-survival Pcdhg-AKT signaling to provide cINs the advantage to survive and integrate. As variants and dysregulated expression of the human PCDH gene cluster are associated with neurodevelopmental and psychiatric disorders including ASD, Tourette's, and schizophrenia (Anitha et al, 2013;El Hajj et al, 2016;Iossifov et al, 2012; Schizophrenia Working Group of the Psychiatric Genomics, 2014; Shao et al, 2019;Vadodaria et al, 2019), these findings also have relevance for understanding the developmental basis of inhibitory deficits in human disorders.…”
Section: The Pcdhgs Are Required For Proper Development Of the Gabaermentioning
confidence: 99%
“…We propose a model in which the extent of PCD among cINs is determined by pro-survival Pcdhg-AKT signaling to provide cINs the advantage to survive and integrate. As variants and dysregulated expression of the human PCDH gene cluster are associated with neurodevelopmental and psychiatric disorders including ASD, Tourette's, and schizophrenia (Anitha et al, 2013;El Hajj et al, 2016;Iossifov et al, 2012; Schizophrenia Working Group of the Psychiatric Genomics, 2014; Shao et al, 2019;Vadodaria et al, 2019), these findings also have relevance for understanding the developmental basis of inhibitory deficits in human disorders.…”
Section: The Pcdhgs Are Required For Proper Development Of the Gabaermentioning
confidence: 99%
“…Previous studies have xenografted hSC-interneurons into a more functionally relevant setting: neonatal mouse cortex. They found that functional maturation rate is prolonged, requiring approximately 7 months (Nicholas et al, 2013;Shao et al, 2019). We then tested the capacity of control and SPARC/SerpinE1-treated ventral organoids to integrate following xenotransplant into immune-compromised (NSG) mouse cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The timescale for interneuron migration varies widely across species; The process lasts days in mice (Lavdas et al, 1999;Marin and Rubenstein, 2001) and several months in humans (Arshad et al, 2016;Hansen et al, 2013;Ma et al, 2013) . Further, this species difference extends to stem cell derived interneurons where mouse ES-derived interneurons develop rapidly (Au et al, 2013;Maroof et al, 2010;, while hSC-interneuron development is protracted (Nicholas et al, 2013;Shao et al, 2019). Indeed, this limitation has restricted the scope of analysis on hSC-interneurons, hampering detailed functional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be interesting to know to what degree rescue of PCDH15 or RELN1 in patients' iPSCs would normalize structural abnormalities. Independent support of a critical role of protocadherins in psychiatric disorders was recently obtained by the transplantation of iPSC-derived cortical inhibitory interneurons (cINs) from healthy controls and patients with SCZ into cerebral cortices of mice [62]. Transplants from either group developed undistinguishably into authentic functioning interneurons in vivo and gene expression profiling of in vitro differentiated cINs uncovered only few DEGs.…”
Section: Private Cnvs At Pcdh15 and Reln Impact Dendrite And Synapse mentioning
confidence: 99%